2012
DOI: 10.1051/0004-6361/201118441
|View full text |Cite
|
Sign up to set email alerts
|

Rocky super-Earth interiors

Abstract: Aims. We present interior structure models of the recently discovered exoplanets CoRoT-7b and Kepler-10b addressing their bulk compositions, present thermal states, and internal dynamics. We investigate how mantle convection patterns are influenced by the depth-dependence of thermodynamic parameters (e.g., thermal expansivity and conductivity) caused by the extended pressure and temperature ranges within rocky super-Earths. Methods. To model the interior of rocky exoplanets, we construct a four-layer structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 68 publications
3
55
1
Order By: Relevance
“…That parametrization is applied in the calculations to the entire silicate mantle. For the Earth test discussed here, the dynamical viscosity (νρ) of the mantle ranges from ∼ 10 20 to ∼ 10 23 Pa s, in accord with the inferred values in the Earth's mantle (Stamenković et al 2011;Wagner et al 2012). The complex rheology of ice, especially of the low-pressure phases, (e.g., Barr & Showman 2009, and references therein), is not meant to be fully accounted for in these calculations.…”
Section: Appendixmentioning
confidence: 53%
See 2 more Smart Citations
“…That parametrization is applied in the calculations to the entire silicate mantle. For the Earth test discussed here, the dynamical viscosity (νρ) of the mantle ranges from ∼ 10 20 to ∼ 10 23 Pa s, in accord with the inferred values in the Earth's mantle (Stamenković et al 2011;Wagner et al 2012). The complex rheology of ice, especially of the low-pressure phases, (e.g., Barr & Showman 2009, and references therein), is not meant to be fully accounted for in these calculations.…”
Section: Appendixmentioning
confidence: 53%
“…For the largest planets Kepler 11c, d, e, and g, the pressure at the base of the H 2 O shell is 160 GPa, so that ppv is the only phase present in their silicate mantles. Post-post-perovskite phases are predicted for P 900 GPa (Wagner et al 2012), a value reached only at the bottom of the mantle of Kepler 11e (although the stability field of post-ppv phases is also determined by temperature, Stamenković et al 2011). The H 2 O shell is mostly in fluid/superionic phase, except for the presence of ice VII layers in the outer parts of Kepler 11c, d and f.…”
Section: Thermal Structures Of the Solid Interiors Of Kepler 11 Plmentioning
confidence: 98%
See 1 more Smart Citation
“…Whereas the low density of GJ 1214b, that has no analogue in the solar system, is attributed to the presence of an extended optically thick hydrogen atmosphere (Rogers & Seager 2011), it has been suggested that carbon-rich solids may predominate the bulk composition of 55 Cancri e (Madhusudhan et al 2012). CoRoT-7b and Kepler-10b, on the other hand, are thought to be composed of silicate rock and iron with the latter concentrated in massive metallic cores (Wagner et al 2012, Swift et al 2012. These compositional trends are roughly followed by the calculated equilibrium surface temperatures, with relatively hot planetary environments along and below the silicate line and colder but still hot environments along and above the water ice line.…”
Section: Resultsmentioning
confidence: 99%
“…where β is the scaling exponent, we first solve the structural equations for mass and momentum assuming hydrostatic equilibrium (e.g., Wagner et al 2012)…”
Section: Methodsmentioning
confidence: 99%